Determinants of health-related quality of life in Iranian patients after recovery from COVID-19: demographic influences and insomnia - Mohsen Saffari; Hormoz Sanaeinasab; Hojat Rashidi-Jahan; Amir Pakpour Hajiagha; Hosein Mahmoudi; Faten Al-Zaben; Harold George Koenig (International Journal of Public Health Science (IJPHS), 2022)
The current study sought to identify factors that may affect health-related quality of life (HRQoL) in patients recovering from COVID-19 infection in Iran. In a cross-sectional study 258 patients diagnosed with COVID-19, participants completed a questionnaire approximately one month after hospital discharge when demographic and clinical factors (including insomnia) and HRQoL were assessed. A logistic regression was used. Age, gender, marital status, education, having child, early physician visit, early diagnosis, early hospitalization, symptom type, Rhesus factor, and level of insomnia were associated with various components of HRQoL (p<0.05). In multivariate analyses, poorer physical HRQoL was independently associated with female gender (OR=4.53; 95% CI=2.22-2.29), initial symptom of cough (OR=2.73; 95% CI=1.26-5.94), and insomnia (OR=2.74; 95% CI=1.22-6.14). Poorer mental HRQoL was associated with being age 40 years or older (OR=1.90; 95% CI=1.02-3.54), female gender (OR=2.48; 95% CI=1.26-4.88), initial symptom being cough (OR=3.12; 95% CI=1.46-6.68), and insomnia (sub-threshold insomnia, OR=3.19; 95% CI, 1.51-6.74, to severe insomnia, OR=3.86; 95% CI=1.35-11.07). Healthcare professionals should be aware that older people, female gender, those with initial symptom of cough, and insomnia may be at greater risk for poor quality of life following hospital discharge.